FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU HIDUP BERSIH DAN SEHAT SEBAGAI UPAYA UNTUK PENCEGAHAN PENYAKIT DIARE PADA SISWA DI SD N KARANGTOWO KECAMATAN KARANGTENGAH KABUPATEN DEMAK - Nia Indriana Sari; Bagoes Widjanarko; Aditya Kusumawati (Jurnal Kesehatan Masyarakat (Undip), 2016)
In 2014 diarrhea cases at Puskesmas Karang Tengah reached 1624 cases with 490 a case that occurred in primary school age children namely 5-14 years. Research aims to understand factors that deals with the clean and healthy living to their students in elementary school of  Karangtowo The kind of research this is quantitative with cross sectional approach. Population in this research 367 respondents with the sample of the 51 respondents. Data analysis using chisquare.The research results show that clean and healthy behaviors to the prevention of disease diarrhea in students 33.3 % of good. While  66.7 % have the clean and healthy living a less well. The knowledge students  52.9 % less than good while 47,1 % good . Attitude students 58,8 % less than good while 41.2 %. As many as 25,5 % of schools support and as many as 74.5 % schools were not supporting a clean and healthy behaviors for the prevention of diarrhea. Facilities infrastructures to do the clean and healthy living owned as many as 27.5 % and infrastructure which is not possessed as many as 72,5 %. The results showed that the correlated  with students in elementary school of  Karangtowo include knowledge ( p = 0.037 ), support the school ( p = 0.016 ), and infrastructure ( p = 0.038 ). While factors that does not affect clean and healthy life behavior in elementary school of  Karangtowo is the age ( p = 0.593 ), sex  ( p = 0.763 ) and attitude ( p = 0.836 ).